EFEKTIVITAS KONSELING KELOMPOK DALAM MENINGKATKAN KEPERCAYAAN DIRI SISWA BROKEN HOME DI SEKOLAH MENENGAH KEJURUAN - Ali Jauhari; Dewi Rayani; Ichwanul Mustakim (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT Family is the primary environment that plays an important role in an individual's psychological development. Family conflicts that end in divorce can lead to a broken home condition which affects children's emotional well-being, such as feelings of sadness, lack of attention, and loss of parental support. These conditions may reduce students’ self-confidence, causing difficulties in social interaction and participation in learning activities. This issue highlights the importance of guidance and counseling services as an effort to help students improve their self-confidence. This study aims to examine the effectiveness of group counseling in improving the self-confidence of tenth-grade students at SMKN 1 Mataram who come from broken home families. The study employed a quantitative approach with a One Group Pre-test and Post-test experimental design. Data were collected through questionnaires as the main instrument, supported by observation, interviews, and documentation. The sample consisted of 8 students selected through purposive sampling from a population of 85 students based on the lowest self-confidence scores. Data were analyzed using the t-test. The results showed that the t-count value of 15.439 was greater than the t-table value of 2.365 at a significance level of 5% (df = 7), indicating that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. These findings indicate that group counseling is effective in improving the self-confidence of students from broken home families. ABSTRAK Keluarga merupakan lingkungan utama dalam perkembangan psikologis individu. Konflik keluarga yang berujung pada perceraian dapat menimbulkan kondisi broken home yang berdampak pada kondisi emosional anak, seperti perasaan sedih, kurang perhatian, serta hilangnya dukungan dari orang tua. Kondisi tersebut berpotensi menurunkan kepercayaan diri sehingga siswa mengalami kesulitan dalam berinteraksi sosial dan berpartisipasi dalam kegiatan belajar. Permasalahan ini menunjukkan pentingnya layanan bimbingan dan konseling sebagai upaya membantu siswa meningkatkan kepercayaan diri. Penelitian ini bertujuan untuk menguji efektivitas konseling kelompok dalam meningkatkan kepercayaan diri siswa kelas X SMKN 1 Mataram yang berasal dari keluarga broken home. Penelitian menggunakan pendekatan kuantitatif dengan desain eksperimen One Group Pre-test and Post-test. Data dikumpulkan melalui angket sebagai instrumen utama, serta observasi, wawancara, dan dokumentasi sebagai data pendukung. Sampel penelitian berjumlah 8 siswa yang dipilih menggunakan teknik purposive sampling dari populasi 85 siswa berdasarkan skor kepercayaan diri terendah. Analisis data menggunakan uji-t (t-test). Hasil penelitian menunjukkan nilai t-hitung sebesar 15,439 lebih besar daripada t-tabel sebesar 2,365 pada taraf signifikansi 5% (db = 7), sehingga Ho ditolak dan Ha diterima. Temuan ini menunjukkan bahwa konseling kelompok efektif dalam meningkatkan kepercayaan diri (self-confidence) siswa dari keluarga broken home.